2009
DOI: 10.2478/v10009-009-0020-x
|View full text |Cite
|
Sign up to set email alerts
|

The food preferences of three-spined stickleback, Gasterosteus aculeatus L., downstream from a dam reservoir

Abstract: Submersed plants appeared in the impounded section of the Warta River as a consequence of low discharge in summer and were colonized by epiphytic fauna dominated by Hydra sp., Simuliidae, and Chironomidae. The three-spined stickleback consumed it voraciously, and their diet composition closely reflected the available food resources. In May their alimentary tracts were filled with Cladocera drifting from the reservoir, and then by the dominant taxa associated with macrophytes, especially chironomid periphyton s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The effect of fish on chironomid community was stronger in site U because fish, mainly young, fed on benthic insects, while similar fish in site D foraged on microcrustaceans (mainly Cladocera, Copepoda, Ostracoda), which occurred both in spring and autumn, and were of reservoir origin (Marszał et al ., 1996). In site D, an additional food base in summer for mainly young fish (perch and ruffe) were epiphytic fauna, such as Chironomidae ( Cricotopus , Parachironomus and Tanytarsini) and Simuliidae (Dukowska et al ., 2009). The foraging of the dominant fish species on chironomids did not seem to limit their abundance owing to their very high P:B ratio (Dukowska, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of fish on chironomid community was stronger in site U because fish, mainly young, fed on benthic insects, while similar fish in site D foraged on microcrustaceans (mainly Cladocera, Copepoda, Ostracoda), which occurred both in spring and autumn, and were of reservoir origin (Marszał et al ., 1996). In site D, an additional food base in summer for mainly young fish (perch and ruffe) were epiphytic fauna, such as Chironomidae ( Cricotopus , Parachironomus and Tanytarsini) and Simuliidae (Dukowska et al ., 2009). The foraging of the dominant fish species on chironomids did not seem to limit their abundance owing to their very high P:B ratio (Dukowska, unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier investigations showed the preferences of three-spined stickleback for the largest (oldest) larvae of the dominant epiphytic dipterans, both simuliids and chironomids (Dukowska et al 2009). In the present study we did not include this kind of data for perch and ruffe, but the same phenomenon was recorded in the case of these two percids.…”
Section: Discussionmentioning
confidence: 93%
“…However, in early autumn each year these hydrophytes have been mechanically damaged and uprooted by large volumes of water released from the reservoir. The trophic relationships within this rich but temporary biotic community have been partially investigated in terms of the primary and secondary invertebrate consumers (gathering collectors, scrapers and predators) and the tertiary consumer, the threespined stickleback, Gasterosteus aculeatus L. (Dukowska et al 1999(Dukowska et al , 2005(Dukowska et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Dukowska et al . () demonstrated that the diet choices of sticklebacks were determined by the available food resources and readily switched from feeding on planktonic Daphnia to epiphytic species on macrophytes. Thus, sticklebacks appear to be somewhat generalist and opportunistic feeders.…”
Section: Introductionmentioning
confidence: 99%